Answer:
17
Step-by-step explanation:
49-32=17
Cud u make me brainliest? Im desperate. Thanks!
Hope this helps!
A. 2x^2 - 3x + 10 = 2x + 21
2x^2 - 3x - 2x + 10 - 21 = 0
2x^2 - 5x - 11 = 0 (quadratic equation)
2x^2 - 6x - 7 = 2x^2
2x^2 - 2x^2 - 6x - 7 = 0
-6x - 7 = 0 (not a quadratic equation)
5x^2 + 2x - 4 = 2x^2
5x^2 - 2x^2 + 2x - 4 = 0
3x^2 + 2x - 4 (quadratic equation)
5x^3 - 3x + 10 = 2x^2
5x^3 - 2x^2 - 3x + 10 = 0 (not a quadratic equation)
Therefore, options a and c can be solved using the quadratic formula.
Answer:
Value of X is 11
Step-by-step explanation:
hope it helps
Answer:
lokókà
haha
Step-by-step explanation:
góbôńìkásó